Cetirizine for the treatment of allergic diseases in children: A systematic review and meta-analysis - Zhou, Pengxiang; Jia, Qiong; Wang, Zhenhuan; Zhao, Rongsheng; Zhou, Wei (Frontiers in Pediatrics, 2022)
Objective: The global prevalence of allergic diseases has led to a negative and extensive impact on the health and lives of children. This study investigates the efficacy, acceptability, and safety of cetirizine (CTZ) for treating pediatric allergic diseases and provides evidence-based assertions. Methods: PubMed, Embase, the Cochrane Library and clinical trials register were searched from inception to April 21, 2022. Randomized controlled trials (RCTs) of children with allergic diseases receiving CTZ compared with those receiving placebo or other drugs were included. Two investigators independently identified articles, extracted data, conducted meta-analyses, assessed the Cochrane risk of bias of individual studies, and evaluated the evidence certainty using the GRADE approach. Primary outcomes included scales that evaluated the recovery of allergic conditions in AR, such as the total symptom score (TSS). Secondary outcomes included laboratory test changes, safety (adverse events, AEs), and quality of life (QOL). Data were pooled using the Cochrane Review Manager, and a fixed-effects model was used if heterogeneity was evaluated as low (I2 < 50%); otherwise, a random-effects model was adopted. Results: A total of 22 studies (5867 patients) were ultimately included (eight with perennial AR, six with seasonal AR, four with atopic dermatitis [AD], and four with other allergic diseases), most of which had a low-to-moderate risk of bias. CTZ was found to benefit allergic symptom control (mean difference of TSS from 1 to 12 weeks, P < 0.05) and QOL in children with AR and had similar efficacy compared with other antihistamines (AHs) or montelukast, without showing better control of AD severity in children. Moderate-to-low certainty evidence demonstrated that CTZ was well tolerated and did not increase the risk of severe and overall AEs, cardiotoxicity, damage to the central nervous and digestive systems, or other systems in children, except for the risk of somnolence (risk ratio, 1.62 [1.02, 2.57], I2 = 9%, P = 0.04, compared with placebo). Conclusions: Moderate-to-low certainty evidence revealed that CTZ could improve clinical improvement and QOL in children with AR and have comparable efficacy with other AHs. CTZ is well tolerated in the pediatric population, except for an increased risk of somnolence.